PENGARUH INTENSITAS CAHAYA DAN JENIS PEMBALUT TERHADAP KEBERHASILAN SAMBUNG PUCUK JAMBU MENTE - Azmi Dhalimi (Pusat Penelitian dan Pengembangan Perkebunan, 2003)
Effect of Light Intensity and Bandage on The Successs ofGrafting of CashewA field trial was conducted at the Cikampek Experimental Garden, Spice and Medicinal Crops Research Institute, from November 1997 to March 1998, aiming at the effect of light intensity and bandage on the success of shoot grafting of cashew (Anacardium occidentale). The experimental was performed with a split-plot design 3 replicat and 10 plant/treatment. The treatments were (1) Light intensity (main plot) consisted of 30% (place under shadow of cashew), 23% (under cinnamon), 27% (under leaves of palm), and 100% (whithout shade). (2) Material for bandage (as sub plot) such as white plastic, black plastic, para film, and selotif. The result showed that the highest number of grafting success was 68,8% obtained by the interaction of white plastic bandage with 30% light intensity, (temperature 320 C, and humidity 60%). The highest shoot was is 16,5 cm, shown by the interaction of white plastic with 100% light intensity. Therefore white plastic color is the best bandage for shoot grafting compared to the other material. There was no interaction effect of light intensity with kind of bandage on the number of leaves.